How can we solve our social problems? - Crone, James A. (Los Angeles : Pine Forge Press, 2011)
"Updated to address recent issues such as the national debate on health care reform, this Second Edition of How Can We Solve Our Social Problems? gives students a sense of hope by demonstrating specific, realistic steps we can take to solve some of the most pervasive social problems in the United States today. Author James A. Crone maintains a sense of sociological objectivity throughout and helps students realize that we can take steps to solve such key social problems as poverty, racial and ethnic inequality, unequal education, and environmental issues. The book's first two chapters define "social problem," provide a theoretical background, discuss the daunting barriers we face in attempting to solve social problems, and demonstrate how sociology can help" "How Can We Solve Our Social Problems? Second Edition, is an excellent supplemental text for courses such as Social Problems, Social Change, Social Policy, Urban Sociology, Public Policy, and Social Welfare in departments of sociology, social work, political science, international studies, and economics"--BOOK JACKET.
1. Preparing to Solve Our Social Problems -- What Is a Social Problem? -- History of Studying Social Problems -- Teaching About Social Problems in Today's World -- How Can Sociologists Address Social Problems and Yet Remain Objective? -- What Social Problem Should We Solve First? -- How Might Sociological Theory Help Us to Solve Social Problems? -- A Theory of Conflict and Social Change: A Way to Better Understand and Therefore Solve Our Social Problems -- Causal Model: A Picture of Our Theory -- My Own Theoretical Orientation -- Other Sociological Theories That Can Help Us Understand and Solve Social Problems -- Concluding Thoughts on Theory and Social Problems -- Addressing Social Problems Within Capitalism -- The Next Chapter -- Questions for Discussion -- 2. Barriers, Possibilities, and How Sociology Can Help -- Barriers to Solving Our Social Problems -- Possibilities for Solving Our Social Problems -- How Can Sociology Help to Solve Social Problems? -- Questions for Discussion -- 3. How Can We Solve the Problem of Increasing Inequality? -- Definition and Statistics -- Causes of Growing Inequality -- Consequences of Growing Inequality -- Options We Have With Inequality -- What Should We Do? -- Questions for Discussion -- 4. How Can We Solve the Problem of Poverty? -- Assumptions We Can Make About Solving Poverty -- What Can We Do? -- Concluding On an Optimistic Note -- Questions for Discussion -- 5. How Can We Solve the Problem of Racial/Ethnic Inequality? -- Now, and Where to Next? -- What Might Racial/Ethnic Equality Mean? -- What More Can We Do? -- Questions for Discussion -- 6. How Can We Solve the Problem of Gender Inequality? -- What Can We Do? -- Concluding Thoughts -- Questions for Discussion -- 7. How Can We Solve the Problem of Unequal Education? -- What Can We Do? -- Problems That Prevent Us From Having Excellent Public Schools -- Tax Money for Schools -- Positive Consequences -- What Will Not Work If We Want Excellent Public Education: The Voucher System -- Questions for Discussion -- 8. How Can We Solve the Problem of Crime? -- What Can We Do? -- A Dilemma: Capitalism and Crime -- Questions for Discussion -- 9. How Can We Solve the Problem of Drugs? -- Keep the Current Policy -- Legalize Drugs for Adults -- Take a Step-by-Step Approach by Legalizing One Drug at a Time -- Where to Go From Here? -- Questions for Discussion -- 10. How Can We Solve the Problem of Health Care? -- Consequences of Our Problem -- Why Don't We Have a National Health Care System Like All Other Industrial Nations? -- Criteria for a New Health Care System -- Elements of a New Health Care System to Satisfy These Criteria -- Advantages of a National Health Care System -- Disadvantages and Costs of a National Health Care System -- What Other Countries Include in Their National Health Care Systems -- The Future: What Could Happen? -- Summer and Fall 2009 and Winter 2010: Finally, Serious Debate -- March 21, 2010: Health Care Reform Passes Congress -- Questions for Discussion -- 11. How Can We Solve the Problems of Families? -- Decreasing Inequality to Help Families -- Decreasing Poverty to Help Families -- Creating Enough Jobs and Enough Decent-Paying Jobs -- Creating Racial/Ethnic Equality to Help Families -- Creating Gender Equality to Help Families -- Including Gay and Lesbian Couples to Help Families -- Decreasing Crime to Help Families -- Changing the Way We Deal With Drugs to Help Families -- Creating a National Health Care System to Help Families -- Creating Good-Quality Education for All Students to Help Families -- Educating Students to Help Families -- Educating Parents to Help Families -- Summary of What We Can Do to Help Families -- Questions for Discussion -- 12. How Can We Solve the World's Population Problem? -- Causes of the World's Population Problem -- What Can We Do? -- Where Are We? -- Questions for Discussion -- 13. How Can We Solve the World's Environmental Problem? -- Consequences -- What Can We Do? -- Conclusio -- Questions for Discussion -- 14. Solving Our Social Problems: Predictions and Conclusions -- A Number of Similar Social Conditions -- Defining a Social Condition as a Social Problem -- Legitimation -- Values and Vested Interests -- Loss of Control Over the Social Problem -- Attention and Resources -- Someone Will Be Dissatisfied -- Compromise -- Becoming Accustomed to Social Change -- Capitalism and Social Problems -- Environment, Population, and Standard of Living -- Building a Sustainable Society -- Conclusion -- Questions for Discussion.
Includes bibliographical references and index.
Keywords: Social problems; Sociology; Social problems -- United States; United States -- Social conditions -- 21st century